Evaluation of Variability in Morphology, Course, and Anatomical Types Observed in Nasopalatine Canal Using CBCT: A Retrospective Study - Simran Singh; Manjula Hebbale; Amit Mhapuskar; Santosh Jadhav; Subharina Mahapatra; Vedika Pillai (Wolters Kluwer Medknow Publications, 2024)
Introduction: With the emerging trends in the dental practice, dental implants remain the up-front choice of replacing edentulous spaces. A detailed assessment of the anatomical landmarks, implant bone dimension, and bone quality evaluation by the radiologist is the key for successful implant placement. Knowledge of the nasopalatine canal anatomy, variability in shape, and possible pathologies associated with it are the mainstay for successful implant placement in maxilla. Aim: The study was conducted with the aim to study variations in morphology, course, and anatomical type of the nasopalatine canal. (NPC). Methodology: A total of two hundred CBCT scans were evaluated to study the variations in morphology, course, and anatomical types of the NPC, and the statical analysis was conducted for the same. Results: A total of two hundred CBCT scans were retrospectively analyzed. The most common morphology of the canal observed was funnel shaped in 52.5%, followed by cylindrical observed in 19.5%. Slanted curved was the most observed course of the canal seen in 38%. On comparing the above two parameters between the gender group, the results were statistically significant for the abovementioned parameters for both the groups (P value < 0.001*). The most common anatomical type observed was Type II which was observed in 67%. Conclusion: NPC is an important anatomical landmark to be considered when any dental procedures like dental implants are planned in anterior maxilla. The knowledge regarding the NPC morphology among the clinicians is of paramount importance in successful placement of implants and also other surgical procedures related to the anterior maxillary region.